2005
DOI: 10.1590/s0100-29452005000300017
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento da laranjera 'Folha Murcha' em sete porta-enxertos no noroeste do Paraná

Abstract: Este trabalho avaliou por um período de 14 anos, em Paranavaí-PR, o comportamento de plantas de laranjeira 'Folha Murcha' enxertadas nos porta-enxertos: limoeiros 'Cravo' (Citrus limonia), 'Rugoso da África' (Citrus jambhiri) e 'Volkameriano' (Citrus volkameriana), citrangeiro 'C-13' (Citrus sinensis x Poncirus trifoliata), trifoliata (Poncirus trifoliata), tangerineiras 'Sunki' (Citrus sunki) e 'Cleópatra' (Citrus reshni). O delineamento experimental utilizado foi o de blocos ao acaso, com sete tratamentos (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
21

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 1 publication
2
6
1
21
Order By: Relevance
“…This characteristic is probably associated with the smaller tree size and canopy volume, a characteristic that may be derived from the parent P. trifoliata (POMPEU JUNIOR, 2005). The data from this study are not consistent with those obtained by Stenzel et al (2005), where no differences in yield efficiency were observed for trees of 'Folha Murcha' sweet orange [C. sinensis (L.) Osb.] grafted onto 'Fepagro C-13' citrange rootstock, as compared to ones with 'Rangpur' lime.…”
Section: Resultscontrasting
confidence: 99%
“…This characteristic is probably associated with the smaller tree size and canopy volume, a characteristic that may be derived from the parent P. trifoliata (POMPEU JUNIOR, 2005). The data from this study are not consistent with those obtained by Stenzel et al (2005), where no differences in yield efficiency were observed for trees of 'Folha Murcha' sweet orange [C. sinensis (L.) Osb.] grafted onto 'Fepagro C-13' citrange rootstock, as compared to ones with 'Rangpur' lime.…”
Section: Resultscontrasting
confidence: 99%
“…Studies have shown that the canopy development of grafts on this rootstock is better than on "Rangpur" (Stenzel et al, 2005a;Auler et al, 2008a). However, "Cleopatra" mandarin rootstocks are more susceptible to water stress than "Rangpur" lime (Pompeu Junior, 2005), probably due to a higher transpiration rate (Cintra et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…Adicionalmente, as recomendações para diversificação de porta-enxertos devem estar baseadas em pesquisas regionais, pois estudos desenvolvidos nas condições edafoclimáticas do Paraná com certas variedades cítricas têm encontrado resultados diferentes daqueles obtidos em outras regiões citrícolas (Stenzel et al, 2005).…”
Section: Behavior Of 'Valencia' Orange Tree On Six Rootstocks In the unclassified